The Relationship Between Stress and Sleep Quality Among Undergraduate Students In The Applied Nursing Program At Poltekkes Kemenkes Palu - Ade Riyani; Jurana Jurana; Helena Pangaribuan; Rahmat Kurniawan (Salando Health Journal, 2026)
Background: Students in health-related study programs frequently experience academic demands, clinical preparation, and organizational responsibilities that may contribute to psychological stress. Stress is known to potentially affect sleep quality and overall well-being. This study aimed to examine the association between perceived stress and sleep quality among undergraduate students in the Applied Nursing Program at Poltekkes Kemenkes Palu. Method: This quantitative analytic study used a cross-sectional design. A total of 77 students were selected from a population of 335 using simple random sampling. Stress levels were measured using the Perceived Stress Scale-10 (PSS-10), while sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). Stress was categorized into mild and moderate levels, while sleep quality was categorized as good or poor based on standard PSQI scoring. Data were analyzed using the chi-square test with a significance level of p < 0.05. Results: Most respondents experienced moderate stress (53 students; 68.8%), while 24 students (31.2%) had mild stress. In terms of sleep quality, 65 students (84.4%) reported poor sleep quality, and 12 students (15.6%) reported good sleep quality. Among students with moderate stress, 94.3% experienced poor sleep quality. The chi-square test showed a significant association between stress level and sleep quality (p = 0.001). The effect size (OR/PR) and 95% confidence interval were not calculated in this analysis. Conclusion: There is a statistically significant association between perceived stress and sleep quality among undergraduate nursing students at Poltekkes Kemenkes Palu. The findings suggest the importance of stress management interventions to support better sleep quality among students